Praktik Manajemen Strategis Pada Masa Pandemi Covid-19: Studi Kasus Pt X Pelaksana Konstruksi Swasta - Rianto, Stefanus; Wijaya, Liliana Inggrit (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Throughout the year of 2020 and 2021, the country of Indonesia is faced with the economic crisis situation caused by the COVID-19 pandemic. The Indonesian goverment has conducted various new up-to-date regulations throughout time accordingly to the latest conditions of the public health in order to prevent the further spread of COVID-19 pandemic, while trying to keep the national economy balanced. X company is one of private costruction builder sector in Indonesia that is impacted by the COVID-19 pandemic. This research is aimed to explore how the COVID-19 pandemic impacts the private construction builder company on the focal of the crisis nowadays, and how the strategic management and crisis management responds in reality from a private construction builder to face the pandemic crisis. The data on this exploratory qualitative research is obtained through direct interviews in X company head office in Surabaya. Four informants are chosen based on the authorization of the management, also from human resource, planning and estimation, health and safety departments. Analysing this qualitative research is done through open coding, axial coding, and selective coding processes. This research found that private construction builder sector is affected negatively in terms of financial, operational, and employee aspects caused by the COVID-19 pandemic, and the dynamic changes of government regulations. The X company management decided to implement various short term strategies consists of retrenchment, persevering, and innovating methods in order to survive during the pandemic crisis. Keywords: COVID-19, crisis impacts, crisis management, exploratory qualitative, private construction